Alligators of Texas - Hayes, Louise, 1957- (Book collections on Project MUSE., 2016)
Found only in the United States, the American alligator ranges in Texas through 120 counties, from the Sabine River to the Rio Grande, across a swath of river drainages and coastal marshes that include both the backwater swamps of the Big Thicket and the urban bayous of greater Houston. From its beginning in a pile of eggs buried in a meticulously constructed nest to its possible end as an alligator burger or a pair of boots, an alligator's habitat preferences sometimes coincide with the favorite haunts of boaters, hunters, and coastal residents. In Alligators of Texas, biologist Louise Hayes.